A qualitative exploration of the views of men working in routine manual occupations, general practitioners and public health strategists about body weight, health and weight management programmes - Broughton, Matthew (2021)
Background Men are underrepresented in weight management programmes despite being more likely to have increased health risk due to elevated body mass index than women. Gender sensitised weight management programmes have been trialled in an attempt to encourage more men to access support. Despite successes little is known about the views of men that have never attended any form of structured weight management programme. The aim of this research was to increase understanding of the views that men least likely to attend weight management programmes have towards body weight, health and weight management programmes.